Receiving the Word in Image Federico Zuccaro’s the Annunciation Broadcast by Prophets (1565) and the Reception History of the Bible in the Counter-Reformation - Church, Chloe (2021)
The Annunciation Broadcast by Prophets (1565) was an altarpiece created by Federico Zuccaro (1541-1609) for the Church of the Annunciation, Rome. It was the first image commissioned by the Order of the Jesuits, a movement involved in propagating the objectives of the Counter-Reformation Church. Altarpieces were particularly effective points of communication between the Catholic Church and the lay beholder, and used visual exegesis as a means to communicate appropriated receptions of biblical texts. The intimate connection that these objects have to their theological and political context marks them as significant moments of biblical reception, that have, up to this point, been overlooked by historians in the field. This article identifies the broader lacuna in scholarship surrounding the reception history of the Bible during the Counter-Reformation. Whilst this is due to a preference for studies of the Bible in the Protestant Reformation, the lack of scholarly investment poorly reflects the relevance of the Counter-Reformation period to the reception-historical methodology. The context prioritized the interpretation of the Bible through the lens of Church tradition, or in other words, the history of the Bible’s reception. This affinity is echoed in the reception-historical approach found in contemporary biblical scholarship, creating a hermeneutical link between the two contexts. Visual culture was a valuable expression of Counter-Reformation rhetoric and visualized the mediation of biblical texts through Church tradition. This article uses Zuccaro’s altarpiece as a tool to argue this hypothesis and postulate the intimate relationship maintained between texts and their reception in Counter-Reformation Catholicism.
Keywords: Altarpieces; annunciation to Mary; biblical reception history; Counter-Reformation